Laparoscopic versus Open Surgery for Hepatocellular Carcinoma: A Meta-Analysis of High-Quality Case-Matched Studies - Ke Chen; Yu Pan; Bin Zhang; Xiao-long Liu; Hendi Maher; Xue-yong Zheng (Canadian Journal of Gastroenterology and Hepatology)
Objective. To present a meta-analysis of high-quality case-matched studies comparing laparoscopic (LH) and open hepatectomy (OH) for hepatocellular carcinoma (HCC). Methods. Studies published up to September 2017 comparing LH and OH for HCC were identified. Selection of high-quality, nonrandomized comparative studies (NRCTs) with case-matched design was based on a validated tool (Methodological Index for Nonrandomized Studies) since no randomized controlled trials (RCTs) were published. Morbidity, mortality, operation time, blood loss, hospital stay, margin distance, recurrence, and survival outcomes were compared. Subgroup analyses were carried out according to the surgical extension (minor or major hepatectomy). Results. Twenty studies with a total of 830 patients (388 in LH and 442 in OH) were identified. For short-term surgical outcomes, LH showed less morbidity (RR = 0.55; 95% CI, 0.47~0.65; P<0.01), less mortality (RR = 0.43; 95% CI, 0.18~1.00; P=0.05), less blood loss (WMD = −93.21 ml, 95% CI, −157.33~−29.09 ml; P<0.01), shorter hospital stay (WMD = −2.86, 95% CI, −3.63~−2.08; P<0.01), and comparable operation time (WMD = 9.15 min; 95% CI: −7.61~25.90, P=0.28). As to oncological outcomes, 5-year overall survival rate was slightly better in LH than OH (HR = 0.66, 95% CI: 0.52~0.84, P<0.01), whereas the 5-year disease-free survival rate was comparable between two groups (HR = 0.88, 95% CI: 0.74~1.06, P=0.18). Conclusion. This meta-analysis has highlighted that LH can be safely performed in selective patients and improves surgical outcomes as compared to OH. Given the limitations of study design, especially the limited cases of major hepatectomy, methodologically high-quality comparative studies are needed for further evaluation.